FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA BERDASARKAN BB/U - AS, Emilda; Alchalidi, Alchalidi; HRP, Meliani Sukmadewi (Jurnal Kesehatan Ibu dan Anak, 2014)
The child nutrition outline the impact of the imbalance betv/een intake and output of nutrients ( nutritional imbalance ) , ie intakeexceeds output , or vice versa , in addition to errors in choosing foods to eat. The fruits of this investments main form of chronicdisease, and less weight, pica, dental caries, as well as allergies .Objective To determine the Factors Affecting Nutritional StatusBased on B/ U In Work Area Health Center Mulia subdistrict of Banda Aceh Banda Majesty Tamiang Year 2013. This researchmethod is an analytical cross-sectional design, population in this study were allmothers toddler (12-59months) and toddlers in theWork Area Health Center District of Banda Banda Majesty Majesty Tamiang district in 2013 amounted to 1110 people . Samplingtechnique in this study using the formula Proportional Stratified Sample of 100 samples . Data collection using questionnaires , thedata weie analyzed using univariate and bivariate frequency distribution tables , cross tables and statistical tests and narrative.Research results showed respondents with good nutritional status as much (75%) , the results of statistical tests with chi-squaretest found the influence of nutritional status of children with maternal knowledge as seen from p value -0.00 and the influence ofnutritional status toddler with family socioeconomic statuswith p value =0.030while the absence of the influence of nutritional statuson maternal occupation with p value = 0.060 .Advice is needed role health workers to be able to provide information about healthprograms , especially on nutritional status of children through outreach to the community , so that the existing knowledge in thecommunity,especially toddlersbecome bettermothers .